Turnkey tyranny? Struggles for a new digital order - Thiel, Thorsten (2017)
Abstract: Networking and digital communication pervade every area of life. As a consequence, norm formation on the Net has become a hotly disputed process. The chapter tracks the evolution of order in Internet politics and correlates this with the emergence of dissidence and its various manifestations. It is argued that dissidence has found a particularly conducive setting for its operations and that, thanks to the open starting position and an astute use of the expanding protest repertoire, it has managed to generate considerable public interest and high legitimacy. To what extent politicisation and dissident practice will succeed, nevertheless, remains to be seen since public approval in the field of Internet politics does not translate easily into effective changes